(untitled) (Baghdad Science Journal, 2017)
This research deals with the qualitative and quantitative interpretation of Bouguer gravity anomaly data for a region located to the SW of Qa’im City within Anbar province by using 2D- mapping methods. The gravity residual field obtained graphically by subtracting the Regional Gravity values from the values of the total Bouguer anomaly. The residual gravity field processed in order to reduce noise by applying the gradient operator and 1st directional derivatives filtering. This was helpful in assigning the locations of sudden variation in Gravity values. Such variations may be produced by subsurface faults, fractures, cavities or subsurface facies lateral variations limits. A major fault was predicted to extend with the direction NE-SW. This fault is mentioned by previous studies as undefined subsurface fault depth within the sedimentary cover rocks. The results of this research that were obtained by gravity quantitative interpretation find that the depth to this major fault plane center is about 2.4 Km.